Penyaringan Paket Berbasis MikroTik untuk Meningkatkan Keamanan Jaringan dan Akses Internet Positif Studi Berbasis Quality Of Service (di SMKS Al-Islam Joresan Mlarak Ponorogo) - Azib Widad Zuhaily Imam; Hanif Al Fatta (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Internet use in educational settings requires secure, controlled network management with good service quality. However, at SMKS Al-Islam Joresan Mlarak Ponorogo, problems persist, including low network security, access to inappropriate content, and suboptimal bandwidth distribution. This study aims to analyze and implement a MikroTik-based packet filtering system to improve network security and support positive Internet access through a Quality of Service approach. The methods used include network requirements analysis, system design using a MikroTik Firewall, implementation of packet filtering and bandwidth management, and network performance testing based on Quality of Service parameters, namely throughput, delay, jitter, and packet loss. The results show that implementing packet filtering can limit access to unwanted sites and significantly improve network security. Furthermore, Quality of Service implementation has been proven to optimize bandwidth usage and improve network stability and service quality. Thus, the integration of packet filtering and Quality of Service is an effective solution for creating a secure, controlled, and high-quality network system in educational settings.